The Impact of Morbid Obesity on In-hospital Outcomes after Revision Total Hip Arthroplasty: An Analysis of the National Inpatient Sample. (5th August 2022) - Hussein, Inaya Hajj; Zalikha, Abdul Kareem; Crespi, Zachary; Tuluca, Andrei; Arapovic, Avianna E.; El-Othmani, Mouhanad M.
Abstract : Introduction: There remain limited data on the effect of obesity on in-hospital outcomes after revision total hip arthroplasty (rTHA). Methods: Discharge data from the National Inpatient Sample were used to identify patients undergoing rTHA from 2006 to 2015. Propensity score analysis was done to analyze the effects of obesity and morbid obesity on in-hospital economic and complication outcomes after rTHA. Results: The estimated 460, 297 rTHAs were done during the study period. Obese patients were more likely to suffer from any complication than not obese patients (41.44% versus 39.41%, P = 0.0085), and morbidly obese patients were more likely to suffer from any complication than obese patients (47.22% versus 41.44%, P < 0.0001). Obesity was associated with increased risk of postoperative anemia compared with not obese patients, while morbid obesity was associated with increased risk of postoperative anemia, hematoma/seroma, wound dehiscence, and postoperative infection ( P < 0.05). Morbidly obese patients also had a significantly greater average length of stay (6.40 days) than obese (5.23 days) and not obese (5.37 days) patients ( P < 0.0001). Discussion: Although both obesity and morbid obesity are associated with higher risk of in-hospital postoperative complications after rTHA, morbid obesity is a larger risk factor and is associated with a longer length of stay.